Evaluation of vibrations in structures using an unconventional optical method - Valera, Aníbal (2007)
This paper presents the result of evaluating the vibrations of a Roof (CISMID / UNI) based on an unconventional procedure, by which the vibration of the structure is produced by quasi-monochromatic sound waves, and the detection of movements vibrations is measured optically by the deflection of a reflected laser beam. Experimentally, 2 prominent resonant frequencies are obtained: 28.5 Hz and 45 Hz, which are identified as the (1,1) and (2.1) resonant modes, respectively.